Development of a guide for drug-nutrient interactions for healthcare professionals - Wijesinghe, W.G.N.; Adikari, A.M.N.T. (Colombo : Sri Lanka Association for the Advancement of Science, 2021)
A large amount of literature is available to suggest that many clinically significant interactions exist between prescription drugs/medications, and the nutrients present in food. Awareness of healthcare professionals (HCPs) about interactions between drugs and food or drugs and nutrients is important to improve patients’ health and prevent adverse effects associated with those interactions. However, easy access to information about drug-nutrient interactions (DNIs) is not always available. Therefore, it is a difficult and complex problem to accurately determine the effects of food and nutrients on a particular drug. The objective of this study was to help the HCPs and adults to become aware of DNIs by developing a booklet (guide) comprised of drug-food and drug nutrient interactions as a printed reference material. Potential DNIs were collected by reviewing the literature and referring drug-related institutional publications of the past 15 years. There were around 145 potential DNIs discovered across 95 different drugs or drug categories. Furthermore, a preliminary survey was conducted to assess the knowledge and awareness of DNIs among 10 participants in each group of physicians, dietitians, pharmacists and adults who were accessible during the Covid-19 pandemic by using a pre-tested interviewer administrated questionnaire. Findings showed that 90% of studied HCPs considered DNIs to manage such interactions while 70% of adults had heard or experienced DNIs. Furthermore, findings of the survey confirmed that lack of information sources was the major barrier of HCPs for managing DNIs. Collected information on potential DNIs were presented in a tabular form under the gastro-intestine disorders, cardiovascular diseases and infectious tabular form. Additionally, mechanisms of DNIs, guidelines for counseling, medical nutrition therapy for medication side effects and micro-nutrient food sources were also compiled as a coloured, pictorial, A5 size booklet. The content validity of the developed booklet was done by doctors, dietitians and pharmacists via an online questionnaire. The developed booklet was simple and user-friendly. Having a booklet with updated information on DNIs for HCPs and adults will be helpful for management of DNIs and prevention from adverse effects of DNIs.
Keywords: Drug-Nutrient Interactions; Food-Drug Interactions; Guide Booklet